1988
DOI: 10.1007/bf00269199
|View full text |Cite
|
Sign up to set email alerts
|

Presence of interferon and anti-interferon in patients with systemic lupus erythematosus

Abstract: Sera from 61 patients with systemic lupus erythematosus (SLE) were serially screened over a period of at least 2 years for IFN and anti-IFN antibodies. IFN concentrations were measured both with a cytopathic effect assay and a more sensitive radioimmunoassay. Of the patients 15% (9/61) had IFN in their serum at one or more occasions as measured in the bioassay (greater than or equal to 6 IU/ml); employing a RIA (greater than or equal to 1 IU/ml) 28% (17/61) of the patients studied were positive for IFN-alpha. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 17 publications
4
48
1
Order By: Relevance
“…Therefore, we suspect that such false-negative results were due to the relatively low sensitivity of the oligonucleotide microarray method, resulting in a bias of the array data toward abundant transcripts. 18 Of the many differentially expressed genes found in our study, changes in protein expression levels have been previously reported including IFN-o, 19 OAS series enzymes, 20,21 ADPRT, 22 and TCR a. 23 A noteworthy finding in our study, is the interferon pathway.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, we suspect that such false-negative results were due to the relatively low sensitivity of the oligonucleotide microarray method, resulting in a bias of the array data toward abundant transcripts. 18 Of the many differentially expressed genes found in our study, changes in protein expression levels have been previously reported including IFN-o, 19 OAS series enzymes, 20,21 ADPRT, 22 and TCR a. 23 A noteworthy finding in our study, is the interferon pathway.…”
Section: Discussionsupporting
confidence: 67%
“…25 Later, IFN-o was found in the sera of SLE, and it may also be a major IFN species produced by peripheral blood cells in SLE patients. 19,20,[26][27][28] In naturally occurring SLE, both circulating IFN-a and increased levels of IFN-a-inducible proteins, such as OAS1, OAS2, and OASL, have been reported. [19][20][21] Because long-term IFN-a therapy of patients with nonautoimmune disorders can induce antinuclear antibodies, antibodies to native DNA and also Fold-change Figure 2 Verification of microarray quantification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-a is another important factor in the development of SLE, and elevated levels of this antiviral cytokine or IFN-a-induced genes are frequently observed in patients with SLE [12][13][14][15]. Activation of the class I IFN system has been confirmed by recent studies using microarray approaches [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Current explanations for the loss of tolerance in states of complement deficiency include impaired elimination of apoptotic bodies [4,5] or dying cells [6] as a source of autoantigens [7,8], and inadequate regulation of follicular B cells via the complement receptor CD21/35 [3], although the absence of CD21, or its most important ligand (C3d), does not seem to be associated with SLE [9,10]. As such, neither model alone can adequately account for the association of complement deficiency and SLE [11].IFN-a is another important factor in the development of SLE, and elevated levels of this antiviral cytokine or IFN-a-induced genes are frequently observed in patients with SLE [12][13][14][15]. Activation of the class I IFN system has been confirmed by recent studies using microarray approaches [16][17][18][19].…”
mentioning
confidence: 99%